Improving specificity of stimulation-based language mapping in stuttering glioma patients: a mixed methods serial case study - Kram, Leonie; Neu, Beate; Schröder, Axel; Meyer, Bernhard; Krieg, Sandro; Ille, Sebastian (Heliyon, 2023)
Objective - Stimulation-based language mapping relies on identifying stimulation-induced language disruptions, which preexisting speech disorders affecting the laryngeal and orofacial speech system can confound. This study ascertained the effects of preexisting stuttering on pre- and intraoperative language mapping to improve the reliability and specificity of established language mapping protocols in the context of speech fluency disorders. - Method - Differentiation-ability of a speech therapist and two experienced nrTMS examiners between stuttering symptoms and stimulation-induced language errors during preoperative mappings were retrospectively compared (05/2018-01/2021). Subsequently, the impact of stuttering on intraoperative mappings was evaluated in all prospective patients (01/2021-12/2022). - Results - In the first part, 4.85 % of 103 glioma patients stuttered. While both examiners had a significant agreement for misclassifying pauses in speech flow and prolongations (Κ ≥ 0.50, p ≤ 0.02, respectively), less experience resulted in more misclassified stuttering symptoms. In one awake surgery case within the second part, stuttering decreased the reliability of intraoperative language mapping. Comparison with Existing Method(s): By thoroughly differentiating speech fluency symptoms from stimulation-induced disruptions, the reliability and proportion of stuttering symptoms falsely attributed to stimulation-induced language network disruptions can be improved. This may increase the consistency and specificity of language mapping results in stuttering glioma patients. - Conclusions - Preexisting stuttering negatively impacted language mapping specificity. Thus, surgical planning and the functional outcome may benefit substantially from thoroughly differentiating speech fluency symptoms from stimulation-induced disruptions by trained specialists.
Gesehen am 09.04.2024